2006
DOI: 10.3892/or.16.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal myxoid chondrosarcoma arising from the clavicle

Abstract: This report presents an extremely rare case of extraskeletal myxoid chondrosarcoma (EMC) arising from the clavicular periosteum. To the best of our knowledge, this may be the first detailed report of its clinicopathological findings. The patient was a 48-year-old man. Plain radiography and CT did not demonstrate any osteolytic lesion or periosteal reaction in the right clavicle. However, MRI showed an isosignal-intensity mass on T1-weighted images and a homogeneous high signal intensity lesion on T2-weighted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 3 publications
3
15
0
Order By: Relevance
“…Low signal foci can be seen on both T1 and T2-WI, and hemorrhagic or myxoid changes may sometimes be recognized on T1-weighted MR images as areas of high signal intensity1, as in our case.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Low signal foci can be seen on both T1 and T2-WI, and hemorrhagic or myxoid changes may sometimes be recognized on T1-weighted MR images as areas of high signal intensity1, as in our case.…”
Section: Discussionsupporting
confidence: 61%
“…A review of the published data revealed that there are two detailed case reports and two case series of clavicular chondrosarcoma, but only the case reported by Nakazora et al1 refers to a primary myxoid extraskeletal chondrosarcoma arising from the clavicle 1,2,6,7. Deik et al8 also reported a case of extraskeletal myxoid chondrosarcoma arising supraclavicularly, causing an interesting clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(J Shoulder Elbow Surg 2008; 17:875-880. ) Whereas primary bone tumors of the clavicle are rare, 1,6,16,26,27,35 radiation-related damage to the clavicle is fairly common, making it somewhat surprising that there are so few reports 33 regarding reconstructive options after wide resection of the clavicle. In a review by Zietz et al 35 from 1954 to 1995 of 312 pediatric patients treated with high-dose radiation therapy to the head and neck, 3 cases of clavicle sarcoma and 2 cases of osteoradionecrosis were found.…”
mentioning
confidence: 96%